Cortinarius (Basidiomycota, Cortinariaceae) section Crassispori revisited: resolving the C. chevassutii complex and demystifying C. variebulbus - Fellin, Alessandro; Calledda, Federico; Frøslev, Tobias Guldberg; Armada, François; Stohn, Geert Schmidt; Brandrud, Tor Erik; Dima, Bálint; Valdagni, Alessandro; Bellanger, Jean-Michel (Phytotaxa, 2024)
Numerous collections made in deciduous and evergreen oak woodlands of Europe allowed us to re-evaluate, both morphologically and molecularly, the systematic position and taxonomic boundaries of Cortinarius chevassutii f. personatus. This infraspecific taxon and Cortinarius chevassutii share the same ecological niche, an identical distribution pattern, and can even co-occur in the same spot, making their distinction quite challenging, morphologically. However, the phylogenetic analysis of our broad dataset supports two reproductively isolated taxa that both deserve the rank of species. According to recent findings, Cortinarius pseudobulliardioides is the name to apply to the former C. chevassutii f. personatus. Based on present knowledge, spore size and average length/width ratio represents the most reliable diagnostic criterion to separate the two species. Additionally, through next generation sequencing (Illumina) of its holotype, we here reveal the phylogenetic position of Cortinarius variebulbus within the same sect. Crassispori. Recent phylogenetically confirmed collections of this species allow us to document and illustrate this taxon for the first time.